THE IMPACT OF PRODUCT QUALITY, PRODUCT DESIGN AND PRICE PERCEPTION INCREASING PURCHASE DECISIONS MEDIATED BY BRAND IMAGE IN LOCK N LOCK INDONESIA - Akbarullah, Alan Aureleo; Silitonga, Parlagutan (Universitas Muria Kudus, 2024)
This research analysis aims to identify the impact of Product Quality, Product Design, Price Perception on Brand Image and Purchasing Decisions in Lock n Lock Indonesia using PLS-SEM to process data. Accidental sampling was used as a sampling technique with 230 respondents who wanted to make a purchase. The research findings have important theoretical implications, showing the positive impact of product quality and price perception on brand image as well as the significant influence of brand image on purchasing decisions. This study also found the negative impact of product quality, product design, price perception on purchasing decisions and product design on brand image. The implications of these findings provide an in-depth look at how companies can design more effective marketing strategies to improve brand image and customer purchasing decisions in Lock n Lock. The study also contributes to the marketing and brand management literature by discussing the complex interactions between product quality, product design, price perception, brand image, and purchasing decisions in the context of the household product industry.